Evaluation of Changes in Protein, Amino Acids, and Flavor during Mixed Fermentation of Chicken and Soybean - Zhengyu LONG; Jinhao ZOU; Huaigu YANG; Guopu REN; Qingming CAO; Daobang TANG (Shipin gongye ke-ji)
In this study, the model of mixed fermentation was constructed using the chicken and soybean, in order to explore its differences (on the content of protein, amino acid nitrogen, free amino acids, volatile flavor substances and on the activity of protease) from a single fermented soybean product. The results showed that fermentation induced a decline of the content of protein, but an increase in amino acid nitrogen, free amino acids and the activity of protease, respectively. Compared with the soybean fermentation group, the mixed fermentation group had significantly higher concentrations of umami amino acids and total free amino acids, and richer volatile flavor substances during fermentation, in which 3-methylthiopropionaldehyde, benzaldehyde, phenylacetaldehyde, and 1-octen-3-ol were regarded as the key differential compounds by means of orthogonal partial least squares discriminant analysis (OPLS-DA) and odor activity value (OAV). The current study contributed to the development of new soybean-based condiment and provided a theoretical reference for quality control of soybean fermentation products.